2019
DOI: 10.1097/mjt.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in Acute Coronary Syndrome: Review of Major Therapeutic Advances

Abstract: Background: In patients with acute coronary syndrome (ACS), a persistent hypercoagulable state has been demonstrated and antithrombin therapy in addition to platelet inhibition has been proposed. Areas of Uncertainty: Vitamin K antagonists (VKAs) were used as oral anticoagulant (OAC) therapy and produced mixed results whereas trials are still ongoing with non-vitamin K OACs (NOACs). Data Sources: A literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Гострі коронарні синдроми є проявами ХКС і, переважно, результатом розриву атеросклеротичних бляшок у коронарних артеріях (КА). Загальними чинниками ризику є паління, АГ, ЦД, дисліпопротеїнемії, чоловіча стать, гіподинамія, сімейна спадкова схильність до розвитку ожиріння, сімейний анамнез раннього ІМ (вік < 55 років) та порушення режиму дієтичного харчування [21][22][23].…”
Section: основні етіологічні чинникиunclassified
“…Гострі коронарні синдроми є проявами ХКС і, переважно, результатом розриву атеросклеротичних бляшок у коронарних артеріях (КА). Загальними чинниками ризику є паління, АГ, ЦД, дисліпопротеїнемії, чоловіча стать, гіподинамія, сімейна спадкова схильність до розвитку ожиріння, сімейний анамнез раннього ІМ (вік < 55 років) та порушення режиму дієтичного харчування [21][22][23].…”
Section: основні етіологічні чинникиunclassified
“…For this reason, CLP is to be withheld for 5 days before surgical procedures. In these situations, it is imperative to consult with the primary prescriber for the CLP [9].…”
Section: Drug Interactionsmentioning
confidence: 99%
“…Because the drug has the potential to cause bleeding, the patient's hemoglobin and other blood counts must be regularly monitored [9]. Although platelet transfusion was recommended by some authors, PATCH trial in 2016 showed a higher three-month death rate in platelet transfused patients [26].…”
Section: Reversal Of Bleedingmentioning
confidence: 99%
“…A family history of early myocardial infarction (55 years of age) is also a high-risk factor. [5][6][7] The classic symptom of ACS is substernal chest pain, often described as a crushing or pressure-like feeling, radiating to the jaw and/or left arm. This classic presentation is not seen always, and the presenting complaint can be very vague and subtle with chief complaints often being di culty breathing, lightheadedness, isolated jaw or left arm pain, nausea, epigastric pain, diaphoresis, and weakness.…”
Section: Introductionmentioning
confidence: 99%